The impact of minimum capital requirements on Zimbabwe commercial banks lending - Chikoko, Laurine; Pierre, Le Roux (Scientific & Academic Publishing, 2016)
The Reserve Bank of Zimbabwe has been revising the minimum capital requirements for banking institutions in line with economic conditions and international banking standards. The paper examines the implications of the Basel Capital Accords minimum capital requirements on Zimbabwean commercial banks lending. In order to ascertain the impact of the minimum capital requirements, panel regression analysis that captures the salient interrelationships between commercial banks lending and capital adequacy requirements was developed. The model includes the commercial bank loans, capital adequacy ratio, bank lending rates and the inflation rates. The results show that stringent capital adequacy requirements have an adverse impact on Zimbabwean commercial banks lending. Reduced bank lending causes a credit crunch in the economy which culminates in stunted economic growth. The results also suggests that commercial banks in Zimbabwe were adjusting their portfolio by switching from higher risk loans to zero risk loans instead of increasing capital provisions. The study recommends the need for the Reserve Bank of Zimbabwe to monitor the financial conditions of the banking sector continuously if monetary policy is to become an effective tool to counter the pro-cyclicality problem inherent in the Basel Accords.